Implementation of Multiple Representation Tests in The Evaluation of Electronics Courses - Tri Isti Hartini; Martin Martin (Faculty of Science and Education, UIN Walisongo Semarang, 2022)
Learning evaluation is a process of measuring and assessing the learning process, in this case, the lecturer measures and assesses students using test instruments. Research on multiple representation-based assessments has been carried out to evaluate electronics courses. The purpose of this study is to present the evaluation results using multiple representation-based assessments in the electronic learning process. This study uses a quantitative approach with a descriptive method. The data sources in this study were physics education students, FKIP UHAMKA. The data collection technique was carried out using a test technique with multiple representation test instruments. The data analysis technique used quantitative descriptive analysis. Testing the effectiveness of the representation test is done through the calculation of the gain score (N-gain). The results of data analysis in this study indicate that the application of multiple representation tests is more effective in determining students' representational abilities on transistor material through verbal formats, mathematical formats, graphic formats, and image formats.